2014
DOI: 10.4236/pp.2014.58094
|View full text |Cite
|
Sign up to set email alerts
|

Antifertility Effects of Aqueous Roots Extract of <i>Alchornea cordifolia</i> (Euphorbiaceae) on Female Albino Rats

Abstract: Aqueous roots extract of Alchornea cordifolia was studied to evaluate its traditional antifertility claim. Antifertility effect of Alchornea cordifolia was evaluated according to the stages of pregnancy of female rats. In the first stage, forty female rats were randomly divided into four groups (10 rats/group) and respectively treated with 1 ml distilled water (control), 100, 200 and 400 mg/kg body weight (BW) per day of Alchornea cordifolia. After laparotomy and at parturition, sites of implantation and resor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…The result revealed significant reduction of serum levels of progesterone by low dose (40 mg/kg) of Ficus sycomorus extract, and this effect might be as a result of inhibition of luteinizing hormone of the anterior pituitary (Blank et al, 2006). It could also be as a result of the alkaloids present in the plant which agrees with findings of Yakubu et al (2008) who reported that the alkaloid component of C. aconitifolious may be behind the reduction in serum progesterone levels, same was reported for the following plants with alkaloidal component: Senna alata leaves (Yakubu et al, 2010), Alchornea cordifolia (Lembe et al, 2014), Dioscorea villosa (Atsukwi, 2015). More so, alkaloids have been reported to inhibit the synthesis of cellular progesterone (Goize et al, 1996).…”
Section: Effect Of Ficus Sycomorus Extract On Serum Concentration Of supporting
confidence: 85%
“…The result revealed significant reduction of serum levels of progesterone by low dose (40 mg/kg) of Ficus sycomorus extract, and this effect might be as a result of inhibition of luteinizing hormone of the anterior pituitary (Blank et al, 2006). It could also be as a result of the alkaloids present in the plant which agrees with findings of Yakubu et al (2008) who reported that the alkaloid component of C. aconitifolious may be behind the reduction in serum progesterone levels, same was reported for the following plants with alkaloidal component: Senna alata leaves (Yakubu et al, 2010), Alchornea cordifolia (Lembe et al, 2014), Dioscorea villosa (Atsukwi, 2015). More so, alkaloids have been reported to inhibit the synthesis of cellular progesterone (Goize et al, 1996).…”
Section: Effect Of Ficus Sycomorus Extract On Serum Concentration Of supporting
confidence: 85%
“…This deterioration is based on a triptych associating sperm quality degradation: hypospermia, oligospermia, azoospermia and asthenospermia [7,8]; increased incidence of testicular cancer and increased abnormalities of the genital tract [9,10]. To this must be added the erectile and ejaculatory dysfunction [11].…”
Section: Introductionmentioning
confidence: 99%